Effect of epstein-barr virus (EBV) encoded latent membrane protein-1 (30 bp deletion mutant) on immune checkpoint regulation in nasopharyngeal and ebv-associated non-nasopharyngeal cancers - Ahmed, Naveed (2024)
Epstein-Barr virus (EBV) is associated with several types of cancer, including nasopharyngeal, breast, gastric, and lungs. Despite previous studies showing a link between the development of Nasopharyngeal carcinoma (NPC) and the identification of EBV’s LMP1-30 bp deletion in NPC patients, several questions remain unanswered. In this research, a comparison of immune checkpoint receptor’s expression levels in 29 patients with EBV-associated NPC, 29 patients with non-NPC cancers, and 29 healthy controls (HC) was determined and evaluated for their association with EBV's LMP1-30 bp deletion mutation. The expression levels of immune checkpoint receptors (CD3, CD4, CD25, CD127, FoxP3, LAG-3, TIM-3, and TIGIT) were accessed on Tregs using flow cytometry assay. While, the detection of cytokine and chemokine concentrations (IL-10, IL-2, IFN-γ, TNF-α, IL-8, and IL-6) were performed using the simple plex assay. Furthermore, the detection of EBV’s LMP1-30 bp deletion mutation (mutant type variant) and LMP1 (wild type variant) from whole blood samples were performed using probe-based real-time PCR (qPCR). The final statistical analysis for association study was performed using different statistical tools. Most of the NPC patients were Malay (79.31%) ethnic, followed by Chinese (20.68%). WHO type III (62.06%) was the most common diagnosis for NPC patients, followed by WHO type II (27.58%) and WHO type I (10.34%). The expression of LAG-3, TIM-3 and TIGIT on Tregs was higher in NPC and non-NPC patients when compared with HC (p<0.05). As compared to non-NPC, the expression of LAG-3 and TIGIT was significantly higher in NPC patients (p<0.05). Although, the expression level of TIM-3 was slightly higher in NPC comparing to non-NPC patients but it was statistically not significant (p=0.053). There was a statistical significance observed when comparing the levels of IL-2, IFN-γ, TNFα, IL-6 and IL-8 (p<0.05) in NPC patients with HCs. However, there was no statistical difference for IL-10 (p=0.054). In case of non-NPC comparison with HCs, the significance was observed for IL-10, and IL-2 (p<0.05), while there was no statistical difference noted for IFN-γ, TNFα, IL-8 and IL-6 (p>0.05). The most dominant cytokine in NPC patients was TNF-α (10.70 ± 4.00 pg/mL); in non-NPC patients, it was IL-8 (13.36 ± 16.41 pg/mL). While IL-2 was found to be the least secreted cytokine in NPC (0.36 ± 0.25 pg/mL) and non-NPC patients (0.21 ± 0.14 pg/mL). The mutant type variant was detected in 27.58% of NPC patients, while none of sample from non-NPC and HC were found positive for the mutant type variant. The wild type variant was detected in 89.65% NPC, 65.51% non-NPC, and 3.44% of HCs. There was no association (p<0.05) found for differences in the expression of immune checkpoint biomarkers in mutant type variant cases with non-mutant type cases. These findings improve our understanding of the effects of EBV's LMP1 on immune checkpoint receptor expression levels in EBV-associated cancer patients. This could help identify potential immune checkpoint inhibitor drugs and predictive biomarkers for monitoring in EBV-associated cancer patients (NPC and non-NPC). Additionally, distinct cytokine profiles highlighted potential differences in the immune response between NPC and non-NPC individuals.